Caffeine consumption and mortality in chronic kidney disease: a nationally representative analysis - Vieira, M (2019)
BACKGROUND: An inverse relationship between coffee consumption and mortality has been reported in the general population. However, the association between caffeine consumption and mortality in patients with chronic kidney disease (CKD) remains uncertain. METHODS: We analysed 4863 non-institutionalized USA adults with CKD [defined by an estimated glomerular filtration rate (eGFR) of 15-60 mL/min/1.73 m2 and/or a urinary albumin:creatinine ratio >30 mg/g] in a nationwide study using the National Health and Nutrition Examination Survey (NHANES) 1999-2010. Caffeine consumption was evaluated by 24-h dietary recalls at baseline and all-cause, cardiovascular and cancer mortality were evaluated until 31 December 2011. We also performed an analysis of caffeine consumption according to its source (coffee, tea and soft drinks). Quartiles of caffeine consumption were <28.2 mg/day (Q1), 28.2-103.0 (Q2), 103.01-213.5 (Q3) and >213.5 (Q4). RESULTS: During a median follow-up of 60 months, 1283 participants died. Comparing with Q1 of caffeine consumption, the adjusted hazard ratio for all-cause mortality was 0.74 [95% confidence interval (CI) 0.60-0.91] for Q2, 0.74 (95% CI 0.62-0.89) for Q3 and 0.78 (95% CI 0.62-0.98) for Q4 (P = 0.02 for trend across quartiles). There were no significant interactions between caffeine consumption quartiles and CKD stages or urinary albumin:creatinine ratio categories regarding all-cause mortality.